(untitled) (Research, Society and Development, 2022)
The monitoring of water resources is essential to meet the vital needs of human beings in addition to being a resource that feeds lines of agro-industrial production and domestic use. The care of this natural resource is subject to several abiotic and biotic changes in reaction to anthropic stimuli. In this study, physical-chemical and microbiological tests were carried out on water samples from homes in the Metropolitan Region of Recife, evaluating the influences of pH, turbidity, alkalinity and chlorides on the presence and density of the microbiota present. The presence of total coliforms, Escherichia coli, Pseudomonas aeruginosa and heterotrophic bacteria were detected. Clostridium perfringens was absent in all samples. The results indicate that the presence of P. aeruginosa showed a negative relationship with turbidity values and a direct relationship with pH, chlorides and alkalinity. Higher chloride concentrations positively and negatively influence the density of coliform bacteria and heterotrophic bacteria, respectively. On the other hand, alkalinity negatively influenced the development of coliforms. The results indicate that the presence of P. aeruginosa showed a negative relationship with turbidity values and a direct relationship with pH, chlorides and alkalinity. Higher chloride concentrations positively and negatively influence the density of coliform bacteria and heterotrophic bacteria, respectively. On the other hand, alkalinity negatively influenced the development of coliforms. Results indicate that the analyzed waters are unsuitable due to the presence of P. aeruginosa, which in turn indicates lack of sanitation in the reservoirs and insufficient chlorination.